The Role of the Committee on the Rights of the Child - Grabowski, Mariusz (International Children’s Rights, 2024)
The Committee on the Rights of the Child was established under Article 43 of the Convention on the Rights of the Child of 1989. According to Articles 43-45 of the Convention, the Committee on the Rights of the Child is treaty-based. The Committee should operate strictly within the express competences established by the Convention and the Optional Protocols. This is a condition for the legality of the Committee’s actions. There is no room for “presumed competencies”. The Committee can only deal with matters that are referred to it under the provisions of the Convention. Therefore, the Committee cannot interfere in matters that fall within the sovereign competence of a State Party to the Convention. Moreover, the Committee is not an authoritative body over the States Parties to the Convention. Even in matters assigned to it by the Convention. Dialogue and advice are the way it operates. The Committee on the Rights of the Child is an important body that protects the rights of children. It has considerable authority as a treaty-based body. Although the Committee does not have “executive” competencies, it significantly influences the application of the law. This can be seen, for example, in the introduction of subsequent provisions of the Convention and Optional Protocols in various countries. This influence is particularly evident in the application of laws. The General Comments issued by the Committee play an important role in stabilising the protection of children’s rights. They create significant standards for legal protection. Owing to the various activities described above, the Committee on the Rights of the Child contributes to spreading legal awareness in individual countries and internationally. Keywords: Child rights, Committee on the Rights of the Child, human rights, United Nations, conventions, international law, child’s best interest, child protection